2021
DOI: 10.1002/nop2.939
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care nurses' experiences with the new electronic medication administration record

Abstract: Aim To explore the experiences of Registered Nurses who administered medications to patients using the electronic medication administration record (eMAR) in Electronic Record for Intensive Care (eRIC) at one adult intensive care unit (ICU) in NSW, Australia. Design The study research design used a qualitative descriptive exploratory approach that took place in two stages. Methods Five participants attended one focus group followed by the observation of each participant as medications were administered to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This was not a pronounced goal for the use of eMAR but instead, an unintended consequence that might add to the understanding of the different views of eHealth between policy makers and health care professionals that now exist. The findings in this study are in line with results from previous research, stating that nurses considered documentation and navigation in the eMAR system as time consuming and took time away from their patient near work [ 16 ]. However, previous research has also stated that using an eMAR does not result in less direct patient care [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was not a pronounced goal for the use of eMAR but instead, an unintended consequence that might add to the understanding of the different views of eHealth between policy makers and health care professionals that now exist. The findings in this study are in line with results from previous research, stating that nurses considered documentation and navigation in the eMAR system as time consuming and took time away from their patient near work [ 16 ]. However, previous research has also stated that using an eMAR does not result in less direct patient care [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…This might be because of resistance among health care workers [ 12 ], who correlate eHealth with threats to essential care values, fear of lost power, and professional integrity [ 13 ]. In a similar manner, eHealth can be experienced by health care professionals as taking focus from patient-centered meetings [ 14 - 16 ] and contributing to an increased amount of documentation and standardization of tasks, with lower staff influence as a result [ 17 ]. Thus, attitudes about eHealth seem to differ between policy makers on the one hand and health care professionals on the other hand.…”
Section: Introductionmentioning
confidence: 99%
“…While eHealth services can facilitate information transmission [26,27], they also have secondary effects that are worth acknowledging. For example, the use of eHealth can contribute to burnout and negatively influence job satisfaction for healthcare professionals [28,29] and working methods and professional roles can be changed in unexpected ways [30][31][32]. Previous research on eMAR has shown that nurses perceive that it can improve medication administration safety and efficiency [25], reduce medication errors [33] and improve documentation compliance [34].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on eMAR has shown that nurses perceive that it can improve medication administration safety and efficiency [25], reduce medication errors [33] and improve documentation compliance [34]. Reported unintended consequences of introducing eMAR include workarounds and documentation challenges [30,35,36]. However, more knowledge is needed on eMAR implementation and its applicability to work environments in home healthcare [37].…”
Section: Introductionmentioning
confidence: 99%
“…This might be because of resistance among health care workers [12], who correlate eHealth with threats to essential care values, fear of lost power, and professional integrity [13]. In a similar manner, eHealth can be experienced by health care professionals as taking focus from patient-centered meetings [14][15][16] and contributing to an increased amount of documentation and standardization of tasks, with lower staff influence as a result [17]. Thus, attitudes about eHealth seem to differ between policy makers on the one hand and health care professionals on the other hand.…”
Section: Introductionmentioning
confidence: 99%